Microwave pyrolysis of oil palm fibres - Arshad Adam, Salema; Ani, Farid Nasir (Faculty of Mechanical Engineering, 2010)

(untitled)
Malaysia and Indonesia are generating millions of ton of oil palm fibres (OPF) from their oil palm mills as biomass solid wastes which needs proper waste utilization application. The main purpose of the present research was to pyrolyse the OPF biomass into bio-oil using microwave irradiation technique. A domestic microwave of 1000 W and 2.45 GHz frequency was modified to accommodate fluidized bed system. It was found that OPF showed poor microwave absorbing characteristics. Therefore, an appropriate microwave-absorbing material such as biomass char was added to initiate the pyrolysis process. Temperature profiles and bio-oil yield was investigated by varying the ratio of OPF to microwave absorber. It was found that the yield of bio-oil depended on the ratio of OPF to microwave absorber. Particular attention on the temperature profiles was also taken into account during microwave heating of OPF. It can be concluded that microwave technique can save significant time and energy through its rapid and volumetric heating characteristics